Characterization of candidate genes related to estrogenic activity in Oreochromis mossambicus - Esterhuyse, Maria M (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Botany and Zoology))--Stellenbosch University, 2008.